Characteristics of TrikotAC as Filter Aids Material for Fabric Filtration System - Hajar, S.; Rashid, M.; Masdiana, N.; Nor Ruwaida, J.; R.Ammar, M. (International Journal of Engineering and Technology, 2026)
Filter aids material applied in fabric filtration system does not merely work as a flue gas cleaning agent but also acts as an efficient particles collection barrier. In this study, the characteristics of a formulated filter aids TrikotAC consisting of three different types of filter aids materials, activated carbon, lime, and PreKot™ were investigated in a laboratory scale filtration unit. Three different formulations of TrikotAC were tested in terms of their pressure drop performance across the filtration unit where the best formulation was determined in the study.
Keywords: Fabric filtration; Filter aids; TrikotAC